In situ propagation-based lung computed tomography for large animal models - D'Amico, Lorenzo; Costello, L.; Nesterets, Y.; Donnelley, M.; Gureyev, T.; Maksimenko, A.; Beck, C.; Ahlers, J.; Smith, R.; How, Y. Y.; Parsons, D.; Hall, C.; et al. (Journal of synchrotron radiation, 2025)
The lung is a complex organ with a hierarchical structure, containing four times more air than tissue. It is in constant contact with environmental factors such as pollution and pathogens, leading to pathological alterations at various hierarchical levels. Because of its intricate structure and continuous movement, lung imaging presents significant challenges for most existing techniques. Recent advancements in phase-contrast computed tomography and photon-counting detectors have greatly enhanced lung imaging capabilities. Specifically, propagation-based imaging (PBI), a phase-contrast method that does not require optical elements, has proven particularly effective at low X-ray dose rates due to the strong phase shifts between lung tissue and aerated regions. This study introduces an in situ imaging approach for large-scale lungs using PBI at the Imaging and Medical Beamline (IMBL) of the Australian Synchrotron. We investigated optimal conditions for PBI, including energy and propagation distance settings, and found that an X-ray beam energy of 70 keV combined with a 7 m propagation distance yields the highest image quality in terms of contrast-to-noise ratio while also delivering the lowest radiation dose. Furthermore, Monte Carlo simulations were performed on the reconstructed volume to calculate absorbed radiation doses in tissues. These findings provide valuable insights for designing future experiments aimed at minimizing radiation exposure and potentially enable in vivo applications in larger animals or even humans.
Online veröffentlicht: 27. Oktober 2025
Gesehen am 19.02.2026